Widening the net: a literature review of antimicrobial agents with potential suitability for outpatient parenteral antimicrobial therapy services—the importance of storage and stability. Issue 2 (3rd December 2021) - Jenkins, Abi; Shanu, Steven; Jamieson, Conor; Santillo, Mark
Abstract : Objectives: Outpatient parenteral antimicrobial therapy (OPAT) services using continuous infusions (CIs) of antimicrobial agents in elastomeric devices require evidence of acceptable stability of the agent over the infusion period. A period of refrigerated storage of filled devices, followed by the CI period, is useful for OPAT services but can present a significant challenge to the stability of drugs. The aims of this study were to review fresh-filled stability data on antimicrobials which would be useful for OPAT services and to identify suitable candidates for further assessment. Methods: Searches identified papers relating to stability assessments of antimicrobials for immediate use tested above 31°C using a stability-indicating method. Results: We identified 18 stability studies published in 12 papers between 2015 and 2020, assessing the stability of 10 agents. Aminopenicillins like ampicillin and amoxicillin appear too unstable for CI, while benzylpenicillin may benefit from buffering to improve its stability. Cephalosporins vary in their stability and CI periods of 24 hours may not be achievable. Of the carbapenems, there are insufficient data for doripenem but meropenem has been extensively studied and is unsuitable for CI longer than 6 hours. Voriconazole may be suitable for CI but needs further investigation. Conclusions: Some drugs identified in our review are unlikely to be suitable for continuous infusion in OPAT services due to instability. Using a 'fresh-fill' approach, without refrigerated storage, may make some drugs useful while other agents should be considered for further assessment to Yellow Cover Document standards. The impact of buffering for penicillins should be assessed further.